Pyopericardium progresses to cardiac tamponade in patient of hypothyroidism due to Staphylococcus aureus (Indian Journal of Case Reports, 2024)
Pyopericardium is a rare condition with a high mortality rate, in which, infection propagates into pericardial space, leading to pus-filled pericardial effusion and cardiac tamponade which can lead to cardiogenic shock and death, if there is any delay in diagnosis and treatment with antibiotics and pericardial drainage. We report the case of a 28-year-old female, a known case of hypothyroidism from the last 6 years who presented with 2 months of fever and recent onset shortness of breath diagnosed as pyopericardium due to Staphylococcus aureus, and having clinical features of cardiac tamponade. She was a known case of hypothyroidism non-compliant with treatment. Pyopericardium conformed with transthoracic 2D echocardiography-guided aspiration of pericardial fluid. After pericardial pus drainage, the patient symptomatically improved initially but remained in shock due to ongoing sepsis and died due to septic shock and multi-organ failure.